2023
DOI: 10.1136/bmjopen-2022-070840
|View full text |Cite
|
Sign up to set email alerts
|

Information provision to caregivers of children with rare dermatological disorders: an international multimethod qualitative study

Abstract: ObjectiveTo identify service-provided information needs among dermatological caregivers of patients living with ichthyosis.DesignThis is the first online international qualitative study to explore caregiver-reported service-provided information needs, using transnational focus groups (n=6), individual interviews (n=7) and in-depth emails (n=5). NVivo facilitated the coding process and Framework Analysis was applied.SettingCaregivers were recruited through two online ichthyosis support groups and resided across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(74 reference statements)
1
0
0
Order By: Relevance
“…Guide ARD patients to establish correct disease perceptions, improve self-management behaviors. The results of this study showed that patients' self-management ability needs to be improved, the participants pointed out that another a considered key in in uencing the coping ability of patients is lack of professional information support, which is consistent with the Walsh's [ 22] nding. It may be related to that most patients passively acquire ARD knowledge and lack the ability to judge the authenticity of Internet related information.…”
Section: Discussionsupporting
confidence: 74%
“…Guide ARD patients to establish correct disease perceptions, improve self-management behaviors. The results of this study showed that patients' self-management ability needs to be improved, the participants pointed out that another a considered key in in uencing the coping ability of patients is lack of professional information support, which is consistent with the Walsh's [ 22] nding. It may be related to that most patients passively acquire ARD knowledge and lack the ability to judge the authenticity of Internet related information.…”
Section: Discussionsupporting
confidence: 74%